Análise de esforços em estruturas rúpteis aplicados a recursos não convencionais em mina de carvão em Candiota, RS - (:unkn) unknown (Universidade Federal do Pampa, 2018)
Unconventional hydrocarbon resources play an important role in the world economy. These resources can be defined as those with permeability below 0.1 mD and continuous regional accumulations independent of structural or stratigraphic traps. This characteristics make the extraction of unconventional hydrocarbons too expensive and complex. There are several types of unconventional resources such as shale gas, coalbed methane, tight gas, tight oil, shale oil, igneous reservoirs, oily sands and fractured and vuggy carbonate reservoirs. To produce this type of resource two associated techniques are applied: drilling of horizontal wells and hydraulic fracturing. Hydraulic fracturing is a method of generating artificial fractures in rocks with low permeability by injecting highly pressurized fluids into a well. The fracturing mechanism can lead to loss of reserves and possibly environmental contamination. Therefore, the structural analysis is important so that there is adequate geomechanical control of the generated fracture network. Most of the natural fractures occur on a sub-seismic scale, limiting the analysis to well profiles and drill cores. This factor, coupled with the low sampling rate of the wells, may generate high uncertainty in geomechanical models. For this reason, the study of analogues is crucial for understanding the variables that control hydraulic fracturing in natural systems. In Brazil, there is occurrence of unconventional hydrocarbons in several regions, one of them is the Paraná Basin. In this basin there is occurrence of coalbed methane associated with layers of coal from the Rio Bonito Formation, located in subsurface. In this work, we analyzed the carbonate rock structures of the Rio Bonito Formation in the Candiota Coal Mine of Companhia Rio Grandense. The aim of the study is to understand the patterns of the region's brittle structures in order to generate stress scenarios for the tendency for sliding, dilation, dilation and slip. The analyzes resulted in the recognition of fractures oriented to NW, N, NE, and normal faults, oriented to N-S and NW-SE, caused by extension regimes. Based on structures with high frequency occurrence, it was determined 24 scenarios combining azimuth and dip direction data. The magnitude of the stress was manipulated in order to compose situations where the stress state is triaxial and compressional and extensional simultaneously. The structures that presented less tendency to dilate and to slide had dip direction opposite to σ1. In situations of greater distensive scenario, most structures tend to slide. The tendency to dilation did not show significant variation with the increase or decrease of the efforts. In situations where σ3 is vertical, areas with less tendency to dilate are concentrated in the regions of the stereogram closer to σ1 and in regions opposite to it. In this way, the study allowed to understand how the structures of the carbonaceous rocks of the Rio Bonito Formation outcropping in Candiota respond to certain regimes of efforts, such as dilation and slip.
Keywords: Recursos não convencionais; Análise de esforços; Modelagem tridimensional; Coalbed Methane; Unconventional resources; Stress Analysis; Tridimensional Modelling; CNPQ::CIENCIAS EXATAS E DA TERRA